The synthesis, crystal chemistry and dielectric properties of AB2O6 euxenite and aeschynite compounds - Gung, Zhi Yang. (2008)
This report describes the synthesis of yttrium-euxenite (euxenite-Y) (Y(Ti0.5Nb0.5)2O6), neodymium-aeschynite (aeschynite-Nd) (Nd(Ti0.5Nb0.5)2O6), and Gd[(SnxTi0.5-x)Nb0.5]2O6, where x = 0.05, 0.125, 0.25 & 0.5, investigates the crystal chemical properties of euxenite-Y and aeschynite-Nd, and surveys the dielectric performance of novel Gd[(SnxTi0.5-x)Nb0.5]2O6 compounds. Both pellets and powders were fabricated. The pellets were examined using scanning electron microscopy (SEM) together with energy dispersive x-ray (EDX) spectroscopy to observe the microstructure, microchemistry and homogeneity. The dielectric performance of Gd[(SnxTi0.5-x)Nb0.5]2O6 and other RE(Ti0.5Nb0.5)2O6 compounds, where RE = Y, Dy, Gd (with euxenite structure) or La, Nd, Sm (with aeschynite structure) pellets were surveyed using impedance/gain-phase analysis. Powders were characterized using powder x-ray diffraction (PXRD) and analyzed by the Rietveld method to refine crystal structures and conduct quantitative phase analysis.